PWE-119 Complex symptom burden and unmet need in end-stage liver disease. (22nd June 2015) - Kriese, S; Bristowe, K; Prentice, WM; Heneghan, MA; Higginson, IJ; Murtagh, FEM
Abstract : Introduction: End-stage liver disease (ESLD) is now the third most common cause of death in those of working age in England and Wales. Despite this, little is known about the palliative care needs of this population, including symptom burden. This study aims to describe the prevalence and severity of symptoms in end-stage liver disease. Method: A cross-sectional survey of adults with ESLD in two UK centres as part of a wider longitudinal study of symptoms, quality of life and other concerns. English-speaking adult patients with Childs Pugh C cirrhosis of any aetiology were eligible for the study. Patients were inelibible if on active antiviral therapy or had persistent grade II (or above) hepatic encephalopathy. Patients were recruited from inpatient and outpatient settings in a tertiary liver unit and a regional liver unit in the southeast of England. Symptoms were assessed using the Intergrated Palliative Care Outcome Scale (IPOS). The IPOS is a ten item questionnaire assessing physical symptoms, emotional, information and support needs in patients with advanced illness. Prevalence and severity of symptoms presented as counts and proportions. Bivariate analysis performed using ordered logistic regression in STATA SE 12.1. Results: We present preliminary data from 27 participants; 67% were male with median age of 55 yrs (IQR 48–60 yrs), mean MELD 17.7 (SD 3.9) and UKELD 53.7 (SD 3.4). Disease aetiology included alcohol (12), PSC (5), NASH (4), PBC (2), viral (2), and other causes (2). Participants reported a median of 8 symptoms of any severity (range 2–13). 75% reported one or more 'severe' or 'overwhelming' symptom (s). The prevalence of severe/overwhelming symptoms largely mirrored the overall prevalence of each individual symptom. The three most common severe symptoms were weakness and lack of energy (46%), drowsiness (34%) and shortness of breath (15%). 24% of particpants reported feeling anxious about their illness most or all of the time. Total number of reported symptoms of any severity and counts of severe/overwhelming symptoms were not associated with age, gender, aetiology, MELD or UKELD. Conclusion: This study demonstrates that patients with ESLD have considerable symptom control needs. These needs are not associated with disease severity as assessed by conventional prognostic scores. Patients with ESLD and may benefit from the earlier integration of specialist palliative care services alongside standard hepatological care. Disclosure of interest: None Declared.